IDENTIFIKASI NILAI PENDIDIKAN SEBAGAI ANALISIS RENCANA DRAMA TARI TOPENG KAYAQ SANDONGAN SEBAGAI MUATAN LOKAL - Sri Sukarni; Lalu Purnama Zulkarnaen; Rohmayadi (JURNAL SANGKAREANG MATARAM, 2020)
This study aimed to describe educational value in the story of Kayaq Sandongan mask dance drama and to analyze the planning of Kayaq Sandongan mask dance drama to be a local content based on its educational value. This study was conducted at Sandongan village where Kayaq Sandongan mask dance drama originated. The method of the study used descriptive analysis method to analyze the relationship between local content and regional potential as well supporting of community and content analysis technique was used to analyze educational value in the story of Kayaq Sandongan mask dance drama. Based on the research findings it is found that religious, social and aesthetics were the three educational values in Kayaq Sandongan mask dance drama. Besides, the community and government of Saribaye village support the implementation of Kayaq Sandongan mask dance drama as local content at SDN I Saribaye because in accordance with regional potential and it aims to cultural preservation.